2015
DOI: 10.1186/s13098-015-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity phenotypes in urban and rural Cameroonians: a cross-sectional study

Abstract: BackgroundDespite the increasing prevalence of diabetes and other health consequences of obesity, little is known on the metabolic profile across categories of body mass index (BMI) among African populations. We therefore assessed the prevalence and distribution of body size phenotypes among urban and rural Cameroonians.MethodsAdults (n = 1628; 41% rural dwellers) aged 24–74 years in 1994 provided data on BMI and metabolic health, defined on the basis of elevated levels of blood pressure (BP); triglycerides, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 20 publications
7
28
3
Order By: Relevance
“…These findings suggest an increasing trend in overweight and obesity in Cameroon, as previous reports in Cameroon showed just over a quarter of the population was overweight [34, 35]. Our findings are similar to reports of a recent systematic review from Nigeria which found rates of 20–35% and 8.1–22% for overweight and obesity respectively [36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest an increasing trend in overweight and obesity in Cameroon, as previous reports in Cameroon showed just over a quarter of the population was overweight [34, 35]. Our findings are similar to reports of a recent systematic review from Nigeria which found rates of 20–35% and 8.1–22% for overweight and obesity respectively [36].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, an overall tendency to overweight was observed in our study population (mean BMI of 25.3 kg/m 2 ). This was marginally higher than previously reported in Cameroon [34, 35]. While the variance may not be striking, it should be noted that the majority of our study population was made up of young adults, almost a decade younger than previous reports in Cameroon [34].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Obesity is associated with an altered metabolic profile, and is a major risk factor for type 2 diabetes mellitus and other cardiovascular disease (CVD) risk factors including hypertension, dyslipidemia and pro-inflammatory states [1]. About 52% of the worldwide adult population is either overweight or obese [2].…”
Section: Introductionmentioning
confidence: 99%
“…A further 'obesity' phenotype includes individuals of normal weight, who have metabolic abnormalities, commonly found in overweight and obese individuals [1,3]. Concepts such as "metabolically healthy" and "metabolically abnormal" have been used to characterize individuals across the distribution of body mass index (BMI) as a function of the underlying burden of metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%